1779 N.C. Sess. Laws 191 - (:unkn) unknown (My University, 1779)
[E]ach Militia Soldier [had to] be furnished with a Good Gun, Shot bag a Cartouch Box or powder Horn, a Cutlass or Tomahawk.
Keywords: MILITIAS